Cicadivetta goumenissa, a new cicada species from Peloponesos, Greece (Hemiptera: Cicadidae) - Gogala, Matija (Acta entomologica slovenica (Ljubljana), 2012)
Near the village of Goumenissa, Peloponesos, Greece, we heard and recorded an unusual and unknown cicada song in the years 2005 and 2006. It was high pitched, hardly audible to humans and therefore we had to use ultrasonic detectors. Later we collected some specimens and found out that it is an undescribed species. Here we publish a description of this new taxon with the name Cicadivetta goumenissa sp. n. In addition to morphological characteristics this species is distinguished by a song pattern with very fast sequences of short echemes (SE, duration 26+_7 ms) of different duration (a few SE up to more than 500 and 37 s duration and repetition frequency of 13-22 SE/s), followed by single long echemes (LE, duration: 535+_88 ms). Exceptionally there are sequences with longer LE echemes (760+_284 ms) and without or just a few SE in-between.
Keywords: Cicadidae; Hemiptera; new species; nove vrste; petje; pojoči škržadi; singing cicadas; songs